Genetika Dasar Prinsip-Prinsip Dasar dari Hereditas Manusia - Anjani, Arum Dwi; Aulia, Devi Lestari Nurul (IAI Nasional Laa Roiba Bogor, 2025)
Mendel's laws of inheritance are the rules regarding the inheritance of characteristics in living things. Currently eye doctors use the Ishihara Test book which contains dots of different colors and sizes to check whether a person suffers from color blindness or not. The blood group system is a method of grouping blood that depends on the antigens in the blood. The division of blood groups generally consists of four types, namely A, B, O, and AB. Thalassemia is a condition of decreased hemoglobin (Hb) synthesis, especially in the globin chain. Hemophilia is a rare genetic disease with a shortened life expectancy.